2004
DOI: 10.1080/14017430410035476
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection with resveratrol pretreatment: improved beneficial effects over standard treatment in rat hearts after global ischemia

Abstract: The findings from this study indicate that RVT has potent cardioprotective properties against I/R injury in rat hearts. The study also highlighted that the administration of RVT, as pretreatment, has amplified the beneficial effects over the standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
2
34
0
2
Order By: Relevance
“…The production of ROS can lead to cell injury through cell membrane lipid destruction and can diffuse intracellularly and cause mitochondrial enzyme damage and cleavage of DNA [43,44] . Recently, resveratrol was found to be a highly potent antioxidant that could inhibit free radical generation in the brain, spinal cord, heart, kidney, liver, red cell membrane, and so on [19,36,[44][45][46][47][48][49] . It has been shown that it inhibits lipid peroxidation [50] , and prevents apoptotic cell death induced by oxidative stress [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…The production of ROS can lead to cell injury through cell membrane lipid destruction and can diffuse intracellularly and cause mitochondrial enzyme damage and cleavage of DNA [43,44] . Recently, resveratrol was found to be a highly potent antioxidant that could inhibit free radical generation in the brain, spinal cord, heart, kidney, liver, red cell membrane, and so on [19,36,[44][45][46][47][48][49] . It has been shown that it inhibits lipid peroxidation [50] , and prevents apoptotic cell death induced by oxidative stress [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported that leptin has a protective effect on renal I/R model induced by 1 hour of ischemia following 1 hour of reperfusion (1). Another study showed the protective effects of resveratrol against oxidative stress on cardiac I/R model in the same time periods (2). Smith et al investigated the role of the JAK/STAT pathway in the cardioprotective effects of resveratrol and suggested that the effects may involve leptin-induced STAT3 phosphorylation (3).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al investigated the role of the JAK/STAT pathway in the cardioprotective effects of resveratrol and suggested that the effects may involve leptin-induced STAT3 phosphorylation (3). Resveratrol, a natural polyphenol compound, has many biochemical and physiological effects, including anti-infl ammatory, antioxidant, antiapoptotic and antiproliferative effects (2). Recent studies have suggested that resveratrol may protect against ischemic damage in skeletal muscle, heart and brain (2,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several ex-vivo studies using isolated perfused hearts subjected to ischemia-reperfusion have reported resveratrol-mediated resistance to myocardial injury (Hung et al 2002;Dernek et al 2004;Mokni et al 2007;Xi et al 2009). These ex-vivo findings have been corroborated in an in-vivo study using an experimental model of acute ischemia-reperfusion injury (Shen et al 2006).…”
mentioning
confidence: 99%